Diagnostic yield of non‐guided flexible bronchoscopy for peripheral pulmonary neoplasia. Issue 4 (22nd January 2015) - Labbé, Catherine; Beaudoin, Stéphane; Martel, Simon; Delage, Antoine; Joubert, Philippe; Drapeau, Christine; Provencher, Steeve
Abstract Background The role of conventional bronchoscopy for peripheral pulmonary neoplasia remains controversial. We aimed to assess the diagnostic yield and the added value of non‐guided bronchial aspiration, bronchoalveolar lavage (BAL), and brushing for the diagnosis of pulmonary neoplasia not visible endoscopically. Methods We retrospectively assessed 207 consecutive patients with a final diagnosis of peripheral lung malignancy who underwent bronchoscopy with non‐guided aspiration, brushing, and BAL as their initial evaluation. The influence of clinical and radiological factors on diagnostic yield was assessed using univariate logistic regression analyses. Results The overall sensitivity of non‐guided bronchoscopy was 25.6%, whereas sensitivities for bronchial aspiration, BAL, and brushing were 14.2%, 11.6%, and 16.5%, respectively. Younger age, larger lesion, central/intermediate distance from the hilum, presence of a bronchus sign, and higher standardized uptake value (SUV) on positron emission tomography scan were predictors of a higher diagnostic yield. Conversely, forced expiratory volume in one second, fellow implication in the procedure, and tumor histology did not influence sensitivity. The overall sensitivity of bronshoscopy was >40% for tumors >4 cm, located in the central/intermediate thirds of the lung, showing a bronchus sign, with an SUV >12 or occurring in patients <50 years of age. Conversely, the sensitivity was <10% for tumors <2 cm, located peripherally or with an SUV <4. Conclusion Neoplasia characteristics may help targeting situations in which conventional bronchoscopy could be used as the initial diagnostic procedure when advanced techniques are unavailable. However, advanced diagnostic tools should probably be proposed as the initial modality for the diagnosis of peripheral malignant lesions when available.